1972
DOI: 10.2172/4670175
|View full text |Cite
|
Sign up to set email alerts
|

Embrittlement of Zircaloy-Clad Fuel Rods by Steam During Loca Transients.

Abstract: One of the possible consequences of a loss-of-coolant accident (LOCA) in a light-water reactor would be the rapid heatup of the fuel tubes in a steam environment. During the period of time in which the cladding was exposed to steam (provided both from boiloff of residual water in the pressure vessel and by the emergency coolant) at elevated temperatures, reaction of the Zircaloy with the steam would cause the formation of an oxide film on the cladding surface and an oxygen gradient into the wall. Since the duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Hobson [16] and Hobson and Rittenhouse [17] performed low-and high-strain-rate ring compression tests, respectively, using two-sided oxidized Zry-4 cladding samples over a wide range of temperatures. The results of the low-strain-rate tests interpolated to ≈135ºC (275ºF) were used to formulate the 1204ºC (2200ºF) peak cladding temperature and 17% maximum oxidation level (Baker-Just ECR [12]).…”
Section: Ductility Determination Using Ring-compression Testsmentioning
confidence: 99%
“…Hobson [16] and Hobson and Rittenhouse [17] performed low-and high-strain-rate ring compression tests, respectively, using two-sided oxidized Zry-4 cladding samples over a wide range of temperatures. The results of the low-strain-rate tests interpolated to ≈135ºC (275ºF) were used to formulate the 1204ºC (2200ºF) peak cladding temperature and 17% maximum oxidation level (Baker-Just ECR [12]).…”
Section: Ductility Determination Using Ring-compression Testsmentioning
confidence: 99%
“…Item (3) cited above would indicate that the ductility loss undergone by the cladding is not determined by absorbed hydrogen alone: The microstructure of the cladding and the absorbed oxygen must also be considered to play some part in the loss of ductility. Nevertheless, it is evident from the other two items (1) and (2) that it is the absorbed hydrogen ,&phase grain boundary. A large number of fine precipitates are observed in the dark region of photograph (d).…”
Section: Causal Relation Between Cladding Embrittlement and Inner Surmentioning
confidence: 99%
“…However the integral tests carried out by Fumihisha et al [7] of cladding rupture indicated a high fracture threshold value of 56% ECR for both non-hydrided and pre-hydrided axially unrestrained cladding. A fractional thickness, the ratio of oxide þ a-Zr(O) phase to initial clad thickness, below which the cladding was reported to be safe by Hobson and Rittenhouse [1] was 0.44 so far as the thermal shock failure was concerned. Considering the clad thickness (0.68 mm) used in their investigation, the combined thickness of ZrO 2 and a-Zr(O) comes to 0.3 mm or 300 mm.…”
Section: Discussionmentioning
confidence: 99%